Researching business and management - Maylor, Harvey; Blackmon, Kathryn L. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2005)
"Researching Business and Management is an introductory text on the process of research in business and management. It will enable you to develop the skills to carry out rigorous research using a systematic approach to the process from defining the research question, through the selection of methods to producing the final report. The authors' style is friendly and supportive, acknowledging the chaos and uncertainty inherent in business projects textbook."--Jacket.
TOC
Includes bibliographical references and index.
BA
Tahur Ahmed
Keywords: Management -- Research; Organizational learning -- Research; Business education -- Research